Finance and Convergence : What's Ahead for Emerging Europe? - Schellekens, Philip; Bems, Rudolfs (Washington, D.C. : International Monetary Fund, 2007)
This paper singles out the key short-term risks and medium-term challenges related to finance and convergence in emerging Europe. With the help of a general equilibrium theoretical framework, the paper identifies pragmatic directions for policymakers. While the "speed limits" to capital inflows may be hard to determine, the costs of breaking them are likely substantial. To ensure "safe driving," policymakers ought to build buffers and reduce vulnerabilities. Equally important, yet often overlooked, is the need to prepare for "the curve ahead"-the reversal of external current account imbalances. To avoid painful adjustments, flexible factor markets and strong financial systems will be more important than ever.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet